A facile access to novel heterocyclic analogues of chalcone from newly synthesized ketone containing isoxazole and a benzoxazinone ring. Issue 56 (25th May 2016) - Verma, Nishant; Kumar, Sumit; Ahmed, Naseem
Abstract : A series of novel heterocyclic analogs of chalcone containing isoxazole and benzoxazinone ring as a prime motif was rationally designed and synthesized. There is nothing in the literature about such α, β-unsaturated ketones. Abstract : A series of novel heterocyclic analogs of chalcone containing isoxazole and a benzoxazinone ring as a prime motif was rationally designed and synthesized. There is nothing in the literature about such α, β-unsaturated ketones. These compounds were synthesized using a Claisen–Schmidt condensation reaction of the ketone precursor with different aromatic aldehydes using ethanol as solvent and piperidine as a base. Our procedure offers easy access to isoxazole and benzoxazinone based chalcone derivatives providing yields in the range of 81–93% within 16 min under mild conditions. Out of 21, 11 compounds were screened for their antibacterial activities. Among the screened compounds, compounds5aj, 5ak and5bj showed excellent antibacterial activities with MIC: 0.34, 0.59 and 0.74 mg ml −1 respectively as compared to standard drugs.